2003
DOI: 10.1007/s000180300028
|View full text |Cite
|
Sign up to set email alerts
|

Stress proteins in neural cells: functional roles in health and disease

Abstract: Heat shock proteins (HSPs) or stress proteins participate in protein synthesis, protein folding, transport and translocalization processes. Stress situations trigger a heat shock response leading to their induction. Similarly, they can be upregulated by impairment of the proteasomal degradation pathway. The upregulation of stress proteins is an important step in prevention of protein aggregation and misfolding after stress, and also is essential during development and differentiation. A number of HSPs are cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(65 citation statements)
references
References 137 publications
(132 reference statements)
4
59
2
Order By: Relevance
“…Tau under normal conditions is a highly soluble protein, and the molecular mechanisms leading to the formation of insoluble aggregates are not yet resolved. The accumulation of abnormally folded proteins, as a result of a variety of stress situations, triggers stress responses that lead to the induction of heat shock proteins (HSPs) (for review, see Richter-Landsberg and Goldbaum, 2003). HSPs act as molecular chaperones that facilitate protein repair and renaturation (Sherman and Goldberg, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Tau under normal conditions is a highly soluble protein, and the molecular mechanisms leading to the formation of insoluble aggregates are not yet resolved. The accumulation of abnormally folded proteins, as a result of a variety of stress situations, triggers stress responses that lead to the induction of heat shock proteins (HSPs) (for review, see Richter-Landsberg and Goldbaum, 2003). HSPs act as molecular chaperones that facilitate protein repair and renaturation (Sherman and Goldberg, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The upregulation of stress proteins is an important step for inhibiting protein aggregation and misfolding following stress (Richter-Landberg and Goldbaum, 2003). To investigate GRP78 mRNA expression in tissues that were exposed to heat stress, fluorescent quantification using the RT-PCR assay was used to quantify GRP78 mRNA expression, and the housekeeping gene GAPDH was used as a reference to normalize GRP78 mRNA levels in order to reduce systematic errors.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, it has been reported that HSP expression plays a protective role and provides tolerance against cellular stress. It is involved in the modulation of proteolytic machinery, preventing protein misfolding and aggregation, thereby accelerating cellular repair processes 32 . In this experiment, voluntary exercise did not alter the level of HSP90 expression when compared to the restraint stress-induced group.…”
Section: Discussionmentioning
confidence: 99%